Land holdings and outward foreign direct investment: Evidence from China. (June 2022) - Ding, Haoyuan; Ni, Bei; Xue, Chang; Zhang, Xiaoyu
Highlights: Land holdings have positive effects on a firm's likelihood, frequency, and value of investing overseas. Firms can obtain better loan terms with land as collateral, thus promoting overseas investment. Non-state-owned enterprises rely on land as collateral in this way more than state-owned enterprises. Land transaction data and OFDI data by Chinese listed firms are combined and analyzed in this study. Abstract: Land transaction data and data on the outward foreign direct investment (OFDI) by Chinese listed firms are analyzed to find that a firm's land holdings have positive effects on its likelihood of investing overseas, the frequency of such investments, and the value invested. We use prefecture-level land supply area and price as instrumental variables to deal with the endogeneity problem and get consistent results. Our analysis suggests that firms can obtain better loan terms with land as collateral, and that more affordable funding promotes OFDI. Non-state-owned enterprises rely on land as collateral in this way more than state-owned enterprises. Such use of collateral is more pronounced for firms operating in provinces with poor local institutions and in host countries with better institutional quality.